Electrospun poly(l‐lactide‐co‐ε‐caprolactone) (PLC) scaffold for tissue engineering - Ye, Yuan. (2011)
Single layer polymeric scaffolds as well as hybrid scaffolds were fabricated from Poly(l-lactide-co-ε-caprolactone)(PLC) copolymers at concentration of 10 wt% (8mL DCM: 2mL DMF) and 12.5 wt%(7mL CHCl3: 1mL DMF) by electrospinning process. Two conditions of fiber diameters were achieved, which were 1.93±0.41 μm (micro scale) and 0.95±0.15 μm (sub-micro scale). Different orientations of fibers in the scaffold were achieved as well including random fibers collected at flat, stationary collector and aligned fibers collected at rotational drum at various rotational speeds from 500rpm to 2500rpm. Scanning Electron Microscopy, 5848 Micro Tester (Instron), Differential Scanning Calorimetry, Porosimetry as well as Contact Angle Meter were utilized to characterize the different properties of fabricated fiber scaffolds.